Knowledge and Practices of Menstrual Hygiene among Adolescent Schoolgirls in Jordanian Badia Region: A Field Study - Yasmeen Qasass; Mohammed ALBashtawy; Khitam Ibrahem Mohammad; Shaher Hamaideh; Wafa'a Ta'an; Ahmad Rayan; Jehan Hamadneh; Shereen Hamadneh; Khetam AL-Awamreh; Ahmad Ayed; Abdullah Alkhawaldeh; Asem Abdalrahim; et al. (Jordan University of Science and Technology, 2023)
Abstract   Background: Normal menstrual cycle is associated with physiological and pathological changes throughout the girls’ lives. It involves physical changes in a girl's body designed to prepare her for pregnancy each month. Significant changes in a girl’s life take place during adolescence and the onset of menstruation. Aims: The study aims to assess the level of knowledge and practices of menstrual hygiene among adolescent schoolgirls in the Jordanian Badia Region. Methods: A cross-sectional study was conducted from February to March 2022. The total number of participants was 550 from six schools for girls in the Badia region. Data was collected using a questionnaire that assessed knowledge and practices of the menstrual cycle. Descriptive statistics (mean, standard deviation, frequency, percentage) and multivariable logistic regression analysis were used to determine the predictors of the level of knowledge and practice of the menstrual cycle. Results: The adolescent schoolgirls have adequate level of knowledge, represented by a percentage of 65. Furthermore, the results show that the overall level of girls’ practices was at a poor level (58%), the highest score was for”Schoolgirls should have a discussion with their mothers about menstruation and what to do during their periods”, and the lowest score was for “If she has to, she will have to change the pads at school”. Moreover, age, mothers’ highest level of education, and family income were the predictors of safe knowledge and practices of the menstrual cycle. Conclusion: Overall, the adolescent schoolgirls are reasonably knowledgeable. Additionally, the girls' overall level of practice was poor and menstrual hygiene knowledge and practices need to be improved. Therefore, health programs concerning knowledge and safe practices of menstrual cycles should be conducted in a school setting.